Analisis Implementasi Fatwa DSN-MUI tentang Akad Ijarah pada Produk Pembiayaan Bank Syariah - Nawal Putri Nabila Huda; Sartiwi Nur Khasanah; Revita Ihda Maul Dina (MONETARIUM: Journal of Economics Business and Management, 2025)
This study analyzes the implementation of the National Sharia Council–Indonesian Ulama Council (DSN-MUI) fatwa on ijarah contracts in Islamic bank financing products. The research focuses on the conformity between ijarah financing practices and DSN-MUI fatwa provisions, as well as the challenges encountered in their implementation. A qualitative approach was employed using case study and document analysis methods, including DSN-MUI fatwas, Islamic banking literature, and ijarah financing practices in Islamic banks. The findings indicate that, normatively, Islamic banks have implemented ijarah contracts in accordance with DSN-MUI fatwas, particularly regarding the clarity of leased objects, determination of ujrah, and the allocation of rights and obligations between parties. Nevertheless, practical challenges remain, such as limited customer understanding of ijarah mechanisms and the complexity of asset management. This study emphasizes that the implementation of DSN-MUI fatwas serves not only as a formal guideline but also as a crucial instrument in ensuring sharia compliance and enhancing customer trust in Islamic banking financing products.